Improving School Literacy through Classroom Management: An Evaluation Using the CIPP Model at SD Negeri Tingkir Lor 02 Salatiga) - Maharani, Kristina; Sanoto , Herry (Jurnal Elementaria Edukasia, 2025)
This research aims to evaluate the effectivveness of the School Literacy Program based on classroom management at SD Negeri Tingkir Lor 02 Salatiga. Through analysis of the context, input, process and product of the program, this research is expected to provide a comprehensive understanding of implementation. The innovation of this research lies in the systematic application of the CIPP evaluation model, with an emphasis on the role of classroom management in supporting increased student literacy. This research uses descriptive qualitative methods to obtain an in-depth understanding of the evaluation of classroom management-based school literacy programs. Data was collected through observation, interviews and document study. The classroom management-based literacy program at SD Negeri Tingkir Lor 02 has shown good result in improving students’ reading skills and building a literacy culture. With improvements in certain aspectes, such as the availability of reading materials, this program could become a sucessful model to be adopted in other schools. Although the results achieved are adequate, there is still room for further development, especially in optimizing the use of literacy fasilities. Overall, the classroom management-based literacy program at SD Negeri Tingkir Lor 02 Salatiga has shown positive results.